Omnichannel marketing communication strategy for Urea fertilizer products: Indonesian case study - Tia Juniati; Z. Hidayat (Institute of Computer Science (IOCS), 2024)
This study was conducted to determine the omnichannel marketing communication strategy for urea fertilizer products implemented by PT Pupuk Indonesia and to analyze the alternative omnichannel marketing communication strategies implemented by PT Pupuk Indonesia based on Porter's Five Forces analysis in Indonesia. This research is qualitative research with a case study research method with data collection techniques in the form of interviews and documentation. The level of competition within the urea industry in the Indonesian market is relatively low in contrast with the global market. The substantial capital required for establishing a new urea plant serves as a deterrent to potential new entrants. Additionally, alternative products capable of replacing the function of urea contribute to this deterrent. The bargaining power of buyers is not particularly significant, given the limited number of competitors in the market. Conversely, the bargaining power of suppliers is considered substantial, attributed to government-regulated regulations concerning raw materials, specifically gas. PT Pupuk Indonesia employs both online and offline media for communication, with a strategic emphasis on online media to enhance data accessibility for stakeholders. The implementation of an omnichannel approach in marketing channels has resulted in an overall increase in fertilizer sales in 2022. Survey findings on customer satisfaction reveal a high level of contentment among customers with the products and services provided.